Brazil's new president and 'ruralists' threaten Amazonia's environment, traditional peoples and the global climate. (24th July 2019) - Ferrante, Lucas; Fearnside, Philip M
Summary: Jair Bolsonaro (Brazil's new president) and "ruralists" (large landholders and their representatives) have initiated a series of measures that threaten Amazonia's environment and traditional peoples, as well as global climate. These include weakening the country's environmental agencies and forest code, granting amnesty to deforestation, approving harmful agrochemicals, reducing protected areas, and denying the existence of anthropogenic climate change. Both the measures themselves and the expectation of impunity they encourage have spurred increased deforestation, which contributes to climate change and to land conflicts with traditional peoples. Countries and companies that import Brazilian beef, soy and minerals are stimulating these impacts.